Response to “Redesigning Systems of School Accountability”: Addressing underlying inequities - Gil, Elizabeth; Kim, Taeyeon (Education Policy Analysis Archives, 2018)
As Bae (2018) suggests, one way to fill gaps between a holistic view of student learning and accountability policy implementation is to use multiple measures that reflect diverse perspectives of learning. The purpose of this commentary is to provide a discussion of issues, which need to be considered in order to achieve the desired outcomes of greater equity and transparency through these broader accountability efforts. In this commentary, we address equity issues related to Bae’s argument and propose that taking action regarding existing inequities in terms of access to resources, and including traditionally excluded voices are crucial to ensuring that new accountability systems meet their intended goal of shared responsibility for deeper learning and continuous improvement.